Strategic human resource management and public employee retention - Marwa Gaber Ahmed Fahim (Review of Economics and Political Science (REPS), 2018)
Purpose - The purpose of this research is to explore the dynamics of using strategic human resource management (SHRM) practices in the public sector. More specifically, this paper tries to point out some main aspects of SHRM, which strongly influence the decision of employees to stay. The empirical study here tends to reveal greater insights into the SHRM-retention relationship and its validation at the National Bank of Egypt (NBE). Design/methodology/approach - This research is co-relational in nature with cause and effect approach. The design of the study is both descriptive in the theoretical part and quantitative in the applied one. Theoretically, this paper adopted the analytical approach to define the main concepts, aside from an empirical study to investigate correlations in practice. Findings - This paper concludes that the employment of best HRM practices is deemed a remarkable strategic tool in the retention of core public employees. Also, the results of analysis provide evidence that SHRM contributes to employee retention at NBE. Practical implications The findings and recommendations of this research can practically guide management to devise effective policies to improve employee retention using appropriate SHRM activities, particularly in the Egyptian public organizations. Originality/value - This research has valuable implications for both theory and practice, as it offers several contributions to literature in the field of study, as well as the practical contribution.
Keywords: 330; Strategic human resource management; Human resource management practices; Employee retention; Public sector; National Bank of Egypt